A programming tool for nonparametric system prediction using Partial Informational Correlation and Partial Weights. (September 2016) - Sharma, Ashish; Mehrotra, Raj; Li, Jingwan; Jha, Sanjeev
Abstract: Identification of system predictors forms the first step towards formulating a predictive model. Approaches for identifying such predictors are often limited by the need to assume a relationship between the predictor and response. To address this limitation, (Sharma and Mehrotra, 2014) presented a nonparametric predictive model using Partial Informational Correlation (PIC) and Partial Weights (PW). This study describes the open source Nonparametric Prediction (NPRED) R-package. NPRED identifies system predictors using the PIC logic, and predicts the response using a k-nearest-neighbor regression formulation based on a PW based weighted Euclidean distance. The capabilities of the package are demonstrated using synthetic examples and a real application of predicting seasonal rainfall in the Warragamba dam near Sydney, Australia. The results show clear improvements in predictability as compared to the use of linear predictive alternatives, as well as nonparametric alternatives that use an un-weighted Euclidean distance. Highlights: Open source R package NPRED for system identification and prediction. Estimate Partial Informational Correlation (PIC) and Partial Weight (PW). Improves predictability compared to existing alternatives.